Jose "Ka Pepe" W. Diokno makatao, makabayan - Sepeda, Bernardo Noceda (Quezon City C & E Pub., 2010)
Life story of Jose W. Diokno, a Filipino human rights activist and nationalist.
Includes bibliographical references (p. 207-220) and index.
College Student
In Tagalog.
Keywords: Diokno, Jose W; Nationalists -- Philippines -- Biography